Lower Versus Higher Exposure to Vasopressor Therapy in Vasodilatory Hypotension: A Systematic Review With Meta-Analysis*. Issue 2 (18th November 2022) - Richards-Belle, Alvin; Hylands, Mathieu; Muttalib, Fiona; Taran, Shaurya; Rochwerg, Bram; Day, Andrew; Mouncey, Paul R.; Radermacher, Peter; Couban, Rachel; Asfar, Pierre; Adhikari, Neill K. J.; Lamontagne, Francois
Abstract : OBJECTIVES: Balancing the risks of hypotension and vasopressor-associated adverse effects is a daily challenge in ICUs. We conducted a systematic review with meta-analysis to examine the effect of lower versus higher exposure to vasopressor therapy on mortality among adult ICU patients with vasodilatory hypotension. DATA SOURCES: We searched Ovid Medline, Embase, and the Cochrane Central Register of Controlled Trials for studies published from inception to October 15, 2021. STUDY SELECTION: We included randomized controlled trials of lower versus higher exposure to vasopressor therapy in adult ICU patients with vasodilatory hypotension without language or publication status limits. DATA EXTRACTION: The primary outcome was 90-day all-cause mortality, with seven prespecified subgroups. Secondary outcomes included shorter- and longer-term mortality, use of life-sustaining therapies, vasopressor-related complications, neurologic outcome, and quality of life at longest reported follow-up. We conducted random-effects meta-analyses to calculate summary effect measures across individual studies (risk ratio [RR] for dichotomous variables, mean difference for continuous variables, both with 95% CIs). The certainty of the evidence was assessed using Grading of Recommendations, Assessment, Development, and Evaluation. We registered this review on the International Prospective Register of Systematic Reviews (CRD42021224434). DATA SYNTHESIS: Of 3, 403 records retrieved, 68 full-text articles were reviewed and three eligible studies included. Lower exposure to vasopressors probably lowers 90-day mortality but this is based on moderate-certainty evidence, lowered for imprecision (RR, 0.94; 95% CI, 0.87–1.02). There was no credible subgroup effect. Lower vasopressor exposure may also decrease the risk of supraventricular arrhythmia (odds ratio, 0.55; 95% CI, 0.36–0.86; low certainty). CONCLUSIONS: In patients with vasodilatory hypotension who are started on vasopressors, moderate-certainty evidence from three randomized trials showed that lower vasopressor exposure probably lowers mortality. However, additional trial data are needed to reach an optimal information size to detect a clinically important 10% relative reduction in mortality with this approach.